If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3 = 3x + 9 Reorder the terms: -3 = 9 + 3x Solving -3 = 9 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -3 + -3x = 9 + 3x + -3x Combine like terms: 3x + -3x = 0 -3 + -3x = 9 + 0 -3 + -3x = 9 Add '3' to each side of the equation. -3 + 3 + -3x = 9 + 3 Combine like terms: -3 + 3 = 0 0 + -3x = 9 + 3 -3x = 9 + 3 Combine like terms: 9 + 3 = 12 -3x = 12 Divide each side by '-3'. x = -4 Simplifying x = -4
| (-1)*(2x+3)=1 | | 4g+4(-6+4g)=1-g | | 3x-3x+12=8 | | 8-3x=3-2x | | 9x+5x=5x+7 | | 4g+3(-8+3g)=1*g | | 8x+12x=120 | | -7x=3x+30 | | 125=r*2.5 | | 22=2l+6 | | z^5-7z^3+5z-1=0 | | x^2-2x=1.1 | | 2+a+4=-1 | | 6n+3=5+6n-2 | | 6x+6=-15 | | x^2-2x-1.1=0 | | -32-5x=4x+12 | | -3-4x=-9 | | 3x^2+15x+12= | | 7y+14=21x | | 10x-126=14x+35 | | -14-7x=-3 | | -5.5=-0.02x^2+x+0.5 | | -5.5=-0.02x+x+0.5 | | 5(n+7)=-44+2(n+6) | | y=-0.02x^2+x+0.5 | | 2x+7-3x=1 | | y=-0.02x+x+0.5 | | 3x+27=10x-33 | | -40=33x+15 | | 3=-x+1 | | 6(2x+1)-3(5x+2)=0 |